Sociology of the professions: what it means for podiatry - King, Olivia (J Foot Ankle Res, 2018)
BACKGROUND: The health professions have progressed and evolved considerably over the last few decades in response to demographic, technological, societal and political changes. They continue to do so as the volume and complexity of population health needs steadily increase. Role boundary expansion is among the key changes to the health professions, including podiatry to meet demand. Nonetheless podiatry’s role boundary expansion has not been achieved swiftly or without resistance from neighbouring and dominant professions. This paper seeks to explain the nature of this resistance with respect to the sociology of the professions literature and to shed light on some of the factors and processes at play when role boundary changes arise in health care. DISCUSSION: Six of the most contemporaneously relevant sociology of the professions theories are summarised: Taxonomic, Marxian, Bourdieusian, Foucauldian, Boundary Work and Neo-Weberian paradigms. CONCLUSION: This review highlights that some paradigms are more relevant than others in the current socio-political landscape. It also illustrates that there is a common theme underlying each approach to defining the professions and their boundaries: competition. This may help health professionals, including podiatrists, to understand and manage the challenges and resistance experienced when professions attempt to expand role boundaries to meet increasing and changing population health needs.